(untitled) (European Journal of Education, 2018)
We have all been students and we have all faced assessment, grades, exams etc. But nowadays there are different methods of assessment that teachers use. Some teachers use the traditional ones, they stay loyal to exams and grades, but others use group projects, portfolios, group discussions etc., which can be more interesting to students and they can find them easier, entertaining and motivating. The purpose of this short research paper is to investigate or examine some ways of assessment which are mostly used by teachers here in Albania, most concretely in one of Elbasan high schools, “Ahmet Dakli”. Attention has been given even to the student’s opinions toward the assessment that they encounter every day. So the study is further observed through questionnaires which allowed me to better arrive to the conclusion.